A study on the perceptions towards the benefit of aural, visual, and kinesthetic strategies in memorization among music students (Performance) in UiTM Shah Alam / Mohd Amirul Asyraf Ngaji - Ngaji, Mohd Amirul Asyraf (Faculty of Music, 2012)
This study was conducted to examine music students' (performance) perception toward the benefit of aural, visual, and kinesthetic strategy in memorization. The purpose of this study is to find out the views and opinions of music students (performance) regarding the benefit of aural, visual, and kinesthetic strategies in memorization. For this particular study, the data are collected from 50 respondents of diploma in music students and another 50 respondents of degree in music performance through questionnaire. The data gathered was analyzed and based on the five research questions. From the finding of this study, it seems that music students have been exposed to aural, visual, and kinesthetic strategies in memorization and these strategies have been prove to give benefit for music performance students in their memorization skills.